LEAD IN FOOD AND ITS CORRELATION WITH BLOOD LEAD LEVELS AMONG PREGNANT WOMEN OF SINDH, PAKISTAN - Naeem, Shahla; Khan, Ayesha Zahid; Sahito, Ambreen; Ghani, Abdul; Rafique, Ghazala; Kayama, Fujio; Fatmi, Zafar (Journal of Ayub Medical College Abbottabad, 2021)
Background: With increasing control of lead (Pb) in gasoline, food has emerged as an important secondary pathway for Pb exposure globally. This study assessed Pb levels in food duplicates and blood. Furthermore, it assessed the correlation of Pb in food duplicates and blood Pb levels with common food items taken by pregnant women of Sindh, Pakistan. Methods: A cross-sectional study was conducted from August 2014 to November 2015, in urban (Karachi) and rural (Gambat, Khairpur) area of Sindh-Pakistan. A total of 103 venous blood samples (Karachi = 63 and Gambat = 40) of pregnant women were measured for blood Pb levels at the time of delivery. One month post-delivery, food frequency questionnaire (FFQ) was administered and three-day food duplicates (same number of cooked portions of food eaten by women) were collected. Food duplicates were analysed for Pb levels. Multivariable linear regression was conducted to identify the frequency of food items which contribute to blood and food Pb levels of pregnant women, separately. Results: With 90% confidence interval, chapati (local flat bread) (Î²=0.20, p<0.001), boiled rice (Î²=0.35, p<0.001), cooked root vegetables (Î²= 0.16, p=0.03), fried savory items (Î²=0.15, p=0.03), sweet snacks (Î²=0.13, p=0.08) were positively associated with elevated mother blood Pb levels. While cream biscuits (Î² =-0.14, p=0.04), lassi (blend of yogurt, water and spices) (Î²= -0.31, p<0.01), market milk desserts (Î²=-0.22, p<0.001), fish (Î²= -0.16, p=0.02), soft drinks (Î²= -0.19, p=0.01) and supari/gutka (betel-nut) (Î²=-0.13, p= 0.06) were negatively associated with mother Pb levels. Tetra-pak market juices (Î²= 0.30, p<0.001) and cooked root vegetables (Î²=0.19, p= 0.05) were positively associated with mother food Pb levels, at 90% CI. Conclusion: Bread, boiled rice, fried savoury items, sweet snacks and cooked root vegetables were contributing to blood Pb levels of pregnant women in Pakistan. These food items may be contaminated with Pb during processing, packaging and storage. Inverse relation of Supari/gutka and soft drinks with blood Pb levels may be due its overall reduction in absorption capacity of the gut for nutrients. Objective individual food item analysis for Pb is warranted for further intervention. Background: With increasing control of lead (Pb) in gasoline, food has emerged as an important secondary pathway for Pb exposure globally. This study assessed Pb levels in food duplicates and blood. Furthermore, it assessed the correlation of Pb in food duplicates and blood Pb levels with common food items taken by pregnant women of Sindh, Pakistan. Methods: A cross-sectional study was conducted from August 2014 to November 2015, in urban (Karachi) and rural (Gambat, Khairpur) area of Sindh-Pakistan. A total of 103 venous blood samples (Karachi = 63 and Gambat = 40) of pregnant women were measured for blood Pb levels at the time of delivery. One month post-delivery, food frequency questionnaire (FFQ) was administered and three-day food duplicates (same number of cooked portions of food eaten by women) were collected. Food duplicates were analysed for Pb levels. Multivariable linear regression was conducted to identify the frequency of food items which contribute to blood and food Pb levels of pregnant women, separately. Results: With 90% confidence interval, chapati (local flat bread) (Î²=0.20, p<0.001), boiled rice (Î²=0.35, p<0.001), cooked root vegetables (Î²= 0.16, p=0.03), fried savory items (Î²=0.15, p=0.03), sweet snacks (Î²=0.13, p=0.08) were positively associated with elevated mother blood Pb levels. While cream biscuits (Î² =-0.14, p=0.04), lassi (blend of yogurt, water and spices) (Î²= -0.31, p<0.01), market milk desserts (Î²=-0.22, p<0.001), fish (Î²= -0.16, p=0.02), soft drinks (Î²= -0.19, p=0.01) and supari/gutka (betel-nut) (Î²=-0.13, p= 0.06) were negatively associated with mother Pb levels. Tetra-pak market juices (Î²= 0.30, p<0.001) and cooked root vegetables (Î²=0.19, p= 0.05) were positively associated with mother food Pb levels, at 90% CI. Conclusion: Bread, boiled rice, fried savoury items, sweet snacks and cooked root vegetables were contributing to blood Pb levels of pregnant women in Pakistan. These food items may be contaminated with Pb during processing, packaging and storage. Inverse relation of Supari/gutka and soft drinks with blood Pb levels may be due its overall reduction in absorption capacity of the gut for nutrients. Objective individual food item analysis for Pb is warranted for further intervention.